2020
DOI: 10.1111/jace.17478
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and rate dependent debonding behaviors of precision glass molding interface

Abstract: The adhesion or sticking of glass on the mold is a major obstacle in multiple glass hot forming techniques, including glass hot embossing, 1 glassware production, 2 as well as precision glass molding (PGM). 3 The chemical reaction and diffusion on the interface 4,5 take much responsibility for the glass-tomold adhesion, due to long-duration contact under high temperature or/and high pressure. In order to reduce the adhesion in PGM, much attention has been paid to mitigate the chemical interactions between glas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…As the macroscale temperature-dependent debonding behaviors have been studied in our previous paper, 27 here we only briefly recall the main findings for coherent understanding. From the front-view photos in Figure 4A, the final shapes of glass specimens can be tremendously altered by the glass/mold adhesion.…”
Section: Macroscale Debonding Behaviors At Different Temperaturesmentioning
confidence: 98%
See 2 more Smart Citations
“…As the macroscale temperature-dependent debonding behaviors have been studied in our previous paper, 27 here we only briefly recall the main findings for coherent understanding. From the front-view photos in Figure 4A, the final shapes of glass specimens can be tremendously altered by the glass/mold adhesion.…”
Section: Macroscale Debonding Behaviors At Different Temperaturesmentioning
confidence: 98%
“…Previously, we investigated the macroscale debonding behaviors of a typical glass molding interface by performing a probe tack test at molding temperature. 27 Separation of the glass/mold interface at molding temperature, instead of during cooling, can determine the adhesion properties at a specific temperature and present the existence and intensity of glass/mold adhesion in a simple and intuitive manner. Here, we continue to study the microscale surface characteristics of the molded glass after debonding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interface coupling mechanism is a complex and dynamic problem that has not been solved completely yet. To clearly understand the interface interactions between glass and mold in glass‐molding process, researchers have done substantial efforts about contact interface behaviors, including sticking, demolding, viscoelastic, frictional, and interface‐thermal resistance 17–21 . Fischbach et al 20 .…”
Section: Introductionmentioning
confidence: 99%
“…To clearly understand the interface interactions between glass and mold in glass-molding process, researchers have done substantial efforts about contact interface behaviors, including sticking, demolding, viscoelastic, frictional, and interface-thermal resistance. [17][18][19][20][21] Fischbach et al 20 investigated the sticking force between coatings and glass interface and analyzed the effect of processing conditions and material characteristics on the adhesion force. The results showed that compression holding time, cooling time, and compression force significantly affected the sticking force, whereas surface roughness, composition of the coatings had no effect on the sticking force.…”
Section: Introductionmentioning
confidence: 99%